2014
DOI: 10.1186/1471-2334-14-128
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus nasal carriage in Ukraine: antibacterial resistance and virulence factor encoding genes

Abstract: BackgroundThe number of studies regarding the incidence of multidrug resistant strains and distribution of genes encoding virulence factors, which have colonized the post-Soviet states, is considerably limited. The aim of the study was (1) to assess the Staphylococcus (S.) aureus nasal carriage rate, including Methicillin Resistant S. aureus (MRSA) strains in adult Ukrainian population, (2) to determine antibiotic resistant pattern and (3) the occurrence of Panton Valentine Leukocidine (PVL)-, Fibronectin-Bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
3
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 32 publications
1
23
3
2
Order By: Relevance
“…The increasing resistance to antibiotics can be connected to antibiotic overuse and requires to be addressed promptly (Netsvyetayeva et al, 2014). The treatment of infections caused by S. aureus has been complicated by antimicrobial resistance in the bacteria (Jackson, Davis, & Barrett, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing resistance to antibiotics can be connected to antibiotic overuse and requires to be addressed promptly (Netsvyetayeva et al, 2014). The treatment of infections caused by S. aureus has been complicated by antimicrobial resistance in the bacteria (Jackson, Davis, & Barrett, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The MRSA colonisation level is considered to be low, when compared with other studies which ranged between 5.9%-15.6% (Nahimana et al, 2006;Wang et al, 2009). Lower MRSA colonization have been reported in some studies, 7.7% in Serbia (Cirkovic et al, 2014), 9.7% in Ukarine (Netsvyetayeva et al, 2014), while high level reported in other studies, 21.2% in Sao Tome and Principle (Conceicao et al, 2013), 36.8% in Iran (Mohajari et al, 2013, 66.4% in Scotland (Matheson et al, 2012), 50% in Libya (El-Bouri and El-Bouri, 2013), 50.5% in Ireland (Huggins et al, 2011). Observed differences in MRSA colonisation level between studies countries and hospitals may be best explained by various factors, microbiological methods (from sampling technique to culture media), local infection control standards, and the local prevalence of MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…One of the remarkable features of this state of pathobiosis is that commensal S. aureus isolates contain many, if not all, of the known virulence factors and microbe-associated molecular patterns (MAMPs) linked to disease (8)(9)(10). The pathogenic potential of these isolates is exemplified by the risk of staphylococcal nasal carriers to develop systemic infections caused by the endogenous S. aureus strain they carry (7,11).…”
mentioning
confidence: 99%